Шлях до цифрової економіки: основні аспекти та виклики для бізнесу - Єременко, Денис Володимирович; Yeremenko, Denys; Єременко, Лариса В'ячеславівна; Yeremenko, Larysa (Запоріжжя : Видавничий дім «Гельветика», 2025)
UA: Цифрова трансформація бізнесу є важливим процесом, що включає впровадження інноваційних технологій для покращення операційної діяльності, оптимізації бізнес-процесів та підвищення конкурентоспроможності. У статті розглядаються основні аспекти цієї трансформації, зокрема вплив цифрових технологій на розвиток організаційних структур, підвищення ефективності управління та розвиток цифрових бізнес-моделей. Окрема увага приділяється ролі людського капіталу, формуванню нових компетенцій та цифрової грамотності працівників. Охарактеризовано важливість інтеграції цифрових рішень у стратегії компаній для досягнення довгострокового успіху. Стаття також аналізує роль інноваційних підходів у забезпеченні стабільного розвитку бізнесу в умовах глобальної цифрової економіки. /// EN: Digital transformation of business is a multifaceted and strategically significant process that involves the integration of advanced digital technologies to enhance operational efficiency, streamline internal processes, and ensure long-term competitiveness in a rapidly evolving market. This article offers a comprehensive exploration of the essential dimensions of digital transformation, focusing on the profound impact of digital tools on organizational development, management effectiveness, and the formation of innovative digital business models. Particular attention is devoted to the central role of human capital, the cultivation of digital competencies, and the importance of fostering digital literacy among employees at all organizational levels. The study emphasizes that digital transformation extends beyond mere technological upgrades—it necessitates systemic organizational restructuring, including shifts in corporate culture, the alignment of business strategies with digital capabilities, and the adoption of agile communication and management frameworks. A holistic approach is advocated, integrating technological advancement with economic rationale and human resource development. The article also investigates the opportunities and challenges associated with the implementation of data analytics, artificial intelligence, and cloud computing, highlighting their transformative potential for sustainable innovation and operational resilience. Moreover, the psychological dimension of digital change is analyzed, with attention to cognitive load, decision fatigue, and human trust in intelligent systems as critical factors influencing adoption. The article proposes a conceptual framework that embeds cognitive systems into strategic planning, enabling organizations to address ethical concerns, data governance, and workforce readiness. By emphasizing human-centered innovation, interdisciplinary collaboration, and adaptive leadership, the study identifies the conditions necessary for dynamic learning, value creation, and sustainable growth in the digital age. It concludes by calling for further psychological research to better integrate cognitive technologies with user behavior and decision-making practices, thereby reinforcing organizational agility and long-term success.
The path to the digital economy: key aspects and challenges for business
Keywords: цифрова трансформація; цифрова економіка; бізнес; інновації; інформаційно-комунікаційні технології; конкуренція; стратегії розвитку; цифрові технології; автоматизація; корпоративна культура; управління; інтелектуальний капітал; цифрові екосистеми; управлінські рішення; digital transformation; digital economy; business; innovations; information and communication technologies; competition; development strategies; digital technologies; automation; corporate culture; management; intellectual capital; digital ecosystems